2021
DOI: 10.1007/s00345-021-03763-w
|View full text |Cite
|
Sign up to set email alerts
|

Robotic radical prostatectomy: difficult to start, fast to improve? Influence of surgical experience in robotic and open radical prostatectomy

Abstract: Purpose The assistance of robotic systems raises the concern of whether there is an improved learning in robotic-assisted radical prostatectomy (RARP) compared to open retropubic radical prostatectomy (ORP). Methods We retrospectively analyzed data from 1438 patients who underwent ORP (n = 735) or RARP (n = 703). For each procedure, the level of experience of three different surgeons was summarized. Perioperative and pathological parameters reflecting surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Recently, Baunack, et al ( 39 ) also compared learning groups of RARP and ORP. In it, the authors identified lower mean age and oncological risk for patients operated on with the robotic technique rather than the open technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Baunack, et al ( 39 ) also compared learning groups of RARP and ORP. In it, the authors identified lower mean age and oncological risk for patients operated on with the robotic technique rather than the open technique.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Baunack, et al ( 39 ), identified that surgeons inexperienced in robotics obtained a higher percentage of PSM and lower yield of dissected lymph nodes. In our study, there was no statistically significant difference in PSM and dissected lymph nodes when comparing the two groups, which gives more credit to robotic surgery Furthermore, Baunack, et al ( 39 ), identified that surgeons inexperienced in robotics obtained a higher percentage of PSM and lower yield of dissected lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] With a projected 288,300 new prostate cancer diagnoses in the United States for 2023 alone, 10 improving assessment and training of nervesparing RARP may substantially improve the quality of life for this patient population. RARP has well-defined milestones within its learning curve, with decreases in operative time after 100 cases, 11 and with erectile function preservation and negative surgical margin plateau beginning at 250 cases. 12 Objective performance indicators (OPIs) are metrics objectively derived from kinematic and event-based data collected from the da Vinci robotic system (Intuitive Surgical).…”
mentioning
confidence: 99%